The effect of waterborne epoxy resin emulsion on the physical properties of oil well cement - Xin, Tang; Yuanguang, Yang; Yingquan, Xie (Penerbit Universiti Kebangsaan Malaysia, 2016)
The main objective of this work was to investigate the influence of waterborne epoxy resin emulsion (WER) on the physical properties of oil well cement slurries. Cement slurries containing 5%, 10% and 15% of WER bwoc were compared with WER-free slurries. The rheological behavior was carried out according to API standard. Uniaxial compressive strength and shear bond strength of cement stone were evaluated at the ages of 24, 48 and 72 h. The experimental results illustrate that the addition of WER does not alter the rheological behavior. The addition of WER has increased the shear bond strength almost 52% at 24 h of aging for 10% WER bwoc when compared with unmodified slurry. The enhancement on shear bond strength was attributed to the mechanical anchoring and resin film forming at the interface.